Effect of Cash Turnover, Receivables Turnover, Asset Turnover, and Market Risk on Company Profitability in the Banking Subsector for the 2022-2024 Period - Rahma fitriani, Itsna; Dyah Ardiyanti, Vika; Rosyadi, Humam (Admisi dan Bisnis, 2026)
This study aims to analyze the effect of cash turnover, receivables turnover, asset turnover, and market risk on profitability, as proxied by Return on Assets (ROA), in banking subsector companies for the 2022-2024 period. The research approach used was quantitative with a purposive sampling technique, resulting in a total of 141 data points from 47 companies. The data analysis technique used multiple linear regression analysis with the help of SPSS 23 software. The results of partial hypothesis testing indicate that the cash turnover variable has a negative and significant effect on profitability, while market risk is found to have a positive and significant effect on profitability. The receivables turnover and asset turnover variables do not show any significant effect on profitability. The results of the coefficient of determination test indicate that the ability of the independent variable to explain the variation in the dependent variable is 19.2%, while the remainder is influenced by other factors outside this research model.